Detached shoot technique to evaluate the reaction of soybean cultivars to Sclerotium rolfsii - Akem, C.; Dashiell, Kenton E. (Elsevier, 1991)
Shoot-tips 15cm long from 15 soybean cultivars and breeding lines were individually immersed in Hoagland's solution in 1 × 14 cm test tubes, and supported by cotton plugs. All leaves were removed leaving about 1 cm of each petiole on the shoot. A 4 mm mycelial plug of Sclerotium rolfsii Sacc., taken from the periphery of a 3-day-old culture grown on acidified potato dextrose agar (PDA) media was placed between the stem and a petiole in the middle of the shoot. Tubes with shoots were then placed in a polyethylene enclosure in a growth room where the day and night temperatures averaged 31 ± 2°C and 24 ± 2°C, respectively. Relative humidity (r.h.) was maintained at 80–90% by lining the bottom of the enclosure with wet burlap. Lesions appeared on shoot tips 2 days after inoculation, and their length was measured 2, 3 and 4 days later. On three cultivars, TG × 1436-1 E, TG × 1596-2E and TG × 1614-1E, the rate of lesion expansion was significantly less than that on the other cultivars. One week after inoculation, tubes were drained, and shoots left in the chamber at 50–60% r.h. to allow sclerotia to form. Sclerotia from each shoot were collected. The cultivars TG × 1436-1 D and TG × 1596-2E produced the fewest sclerotia per shoot-tip. Sclerotial viability, determined by germination on PDA at 25 ± 2°C in darkness, ranged from 38 to 99%. This method is effective in differentiating reactions of soybean cultivars to S. rolfsii.